Evaluation and Utilization of Kuantan Clayey Soil as Material Embankment for Roadway - Achmad Fauzi, Abdul Wahab; Kusbiantoro, Andri; Djauhari, Zuraidah; Fauzi, Usama Juniansyah (2014)
In general, clayey soil was used as material embankment for increasing road way level before road structure being constructed. Some types of clay are expansive soil, its have been contributing to pavement failures and subsequently causing increased annual maintenance expenditure of the road. The pavements design/redesign methods are found to be the primary cause of these failures. Thus, it is quite important to investigate the Kuantan clay properties so that can improve the embankment performance and to propose the engineering properties chart for utilization these soil as material embankment.This paper was evaluated and utilized of the engineering properties of Kuantan clayey soil as material embankment for roadway. The research were conducted soil engineering properties, standard compaction, four days soaked California Bearing Ratio (CBR) test to ten clayey soil samples from various sites in Kuantan. The 4 days soaked CBR of clayey soil samples were prepared at optimum water content. The chemical element was investigated by Integrated Electron Microscope and Energy-Dispersive X-Ray Spectroscopy (SEM-EDS) and linear regression analysis were used to anlyzing relation among engineering properties variables.